PENGARUH VARIASI PENGADUKAN SERBUK ALUMINIUM (AL), MAGNESIUM (MG), DAN SENG (ZN) TERHADAP SIFAT MEKANIK LOGAM DENGAN METODE METALURGI SERBUK - Mahadi S.T., M.T; Rayhan Novri (DINAMIS, 2020)
The use of aluminum is often found The mechanical properties of aluminum that are lightweight and rust resistant are among the reasons aluminum is often used for certain raw materials. However, the mechanical properties of aluminum if the levels are pure will not be suitable for the purpose of use, because the value of hardness is very small. Therefore aluminum to add mechanical properties need to be added to other alloy compounds. This study focused on the addition of magnesium (Mg) and Zeng (Zn) alloys with 3 variations, namely the first variation of aluminum 100%, the second variation of aluminum 95%, magnesium 2.5%, zinc 2.5%, third variation of aluminum 90%, magnesium 5%, 5% zinc. From the results of the hardness test, tensile test and impact test, the highest value is found in the third variation. Whereas for the third specimen metallographic test porosity occurs slightly due to the uniformly distributed filler and matrix